2012
DOI: 10.1007/s00701-011-1269-x
|View full text |Cite
|
Sign up to set email alerts
|

Post-traumatic thoracic outlet syndrome

Abstract: The majority of patients suffering from a post-traumatic TOS present a neurogenic, usually subjective syndrome. Prompt therapeutic management is necessary, addressing both physical and psychological complaints. Most patients are cured or well improved by conservative and/or surgical treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Clavicular or rib fractures causing TOS have been described, but most frequently in the setting of motor vehicle accidents [6], and infrequently in athletes [7]. In fact, isolated traumatic rib fractures in athletes without resulting TOS are rare, further underscoring the infrequent incidence of subsequent TOS in this population [8, 9].…”
Section: Discussionmentioning
confidence: 99%
“…Clavicular or rib fractures causing TOS have been described, but most frequently in the setting of motor vehicle accidents [6], and infrequently in athletes [7]. In fact, isolated traumatic rib fractures in athletes without resulting TOS are rare, further underscoring the infrequent incidence of subsequent TOS in this population [8, 9].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we instructed the patient to pay more attention to performing conservative treatment, including modification of behavior patterns and postural correction after endovascular reconstruction of bilateral upper limbs' blood flow. Many previous studies (22)(23)(24)(25)(26) have also found that conservative treatment should be the initial treatment for TOS except in cases of acute thromboembolism and progressive neurological insufficiency (25,27,28). Whether the surgery treatment is necessary for TOS is still controversial (29).…”
Section: Discussionmentioning
confidence: 99%
“…The predisposed thoracic outlet can be decompressed by the sudden force received at this location at the time of injury. Decompression can occur quickly and most often lead to a neurogenic type of TOS, which several authors in the literature [21,117,121,122].…”
Section: Pathophysiology-trauma Of the Shoulder Or Neckmentioning
confidence: 99%
“…TOS can occur after fractures of the FR, the transverse process of C7, or the clavicle; eight patients with developed TOS in this pathomechanism were described by Dubuisson et al [122]. In 1973, Mulder described a few patients who had various forms of TOS after trauma to the collarbone, cervical spine, shoulder, or FR [123].…”
Section: Pathophysiology-trauma Of the Shoulder Or Neckmentioning
confidence: 99%